Bioanalytical study by HPLC for Quantification of Drug in Plasma Blood Concentration - Vaishnavi A Shirsath; DR. Kaveri M Nannor; Pallavi k Danke; Rutuja D Khare; Sakshi B Vanjul (Asian Journal of Pharmaceutical Research and Development, 2025)
Bioanalytical quantification plays a vital role in pharmaceutical, clinical, and toxicological biological matrices such as plasma, serum, urine, and tissues. These measurements support the evaluation of pharmacokinetic (ADME) behavior, therapeutic effectiveness, and drug safety. However, biological matrices contain numerous endogenous substances that can introduce matrix effects, affecting extraction efficiency, chromatographic separation, and detector response, thereby reducing accuracy and sensitivity. High-Performance Liquid Chromatography (HPLC) is a highly reliable analytical technique widely used for the separation and quantification of analytes in complex samples due to its superior selectivity, precision, and reproducibility. Method development in HPLC involves careful selection of stationary and mobile phases, optimization of chromatographic conditions, and appropriate detection strategies such as UV, fluorescence, and LC–MS/MS. Robust sample preparation methods—including protein precipitation, liquid–liquid extraction, and solid-phase extraction—are essential to minimize matrix interference and enhance analytical performance. Regulatory validation ensures compliance with accuracy, precision, linearity, stability, and selectivity requirements for routine application in bioanalysis. Continuous advancements in UHPLC, hyphenated techniques, automation, and green analytical approaches are further improving throughput, sensitivity, and sustainability. Thus, HPLC-based bioanalytical quantification remains indispensable for drug development, therapeutic drug monitoring, and personalized medicine.